1995
DOI: 10.1590/s0102-311x1995000100016
|View full text |Cite
|
Sign up to set email alerts
|

A decisão de abortar: processo e sentimentos envolvidos

Abstract: In Brazil, induced abortion is considered a crime in the majority of cases, the result being that there is little official data on the subject. Little is known about the conditions under which abortions are induced This research was designed to shed light on the characteristics of the women who had had an abortion and to study the reasons why and conditions under which it occurred. The sample consisted of all employees (7,359) and students (2,231) in a university program in S o Paulo who were mailed a self-adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
28

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 4 publications
(3 reference statements)
0
9
0
28
Order By: Relevance
“…Na maioria das vezes, a sociedade encara a decisão pela interrupção da gestação como uma decisão egoísta da mulher, desafiando códigos legais e morais 29 ; entretanto, sabe-se que o abortamento leva a grande sofrimento físico e emocional. Osis e colaboradores 26 , ao estudarem a razão que levou mulheres a desistirem de abortar, destacam que o medo de serem presas não foi citado; os motivos citados foram relacionados às conseqüências de âmbito físico, psicológico e moral.…”
Section: Discussionunclassified
“…Na maioria das vezes, a sociedade encara a decisão pela interrupção da gestação como uma decisão egoísta da mulher, desafiando códigos legais e morais 29 ; entretanto, sabe-se que o abortamento leva a grande sofrimento físico e emocional. Osis e colaboradores 26 , ao estudarem a razão que levou mulheres a desistirem de abortar, destacam que o medo de serem presas não foi citado; os motivos citados foram relacionados às conseqüências de âmbito físico, psicológico e moral.…”
Section: Discussionunclassified
“…A relative could make such a decision difficult, gi- ven the cultural importance of pregnancy and the legislation in force in Brazil. 16 One study 17 indicates that women that only talk with friends about the pregnancy and the possibility of abortion interrupted the pregnancy more than those who contacted other people. The hypothesis is that, while friends tend to support other life projects, closer family tend to value motherhood and influence maintaining the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although friends are sought out when discovering the pregnancy, the woman's decision on the future of the pregnancy varies according to the reactions of their partner or how they imagine their partners would react. [17][18][19] In this study, the partner not knowing about the pregnancy was associated with induced abortion, which could indicate either their lack of involvement or indicate the woman's choice not to include him at the time. The presupposition of male rejection of unplanned or unwanted pregnancy makes many women choose to assume the responsibilities and the decisions, and not inform their partner about the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to abort is never taken alone and it is an experience that is not easy to face, as other studies in Brazil have shown (Costa et al, 1995;Ramirez-Galvez, 1999;Menezes, 2006;Heilborn et al, 2012;Silveira, 2014). When a woman reaches the conclusion that an abortion is "the only way out," she has already considered a variety of negative issues, such as: the fact that abortion is a crime; the difficulties involved in trying to find the means to provoke an abortion; the opposition from partners, relatives, and others; information that the procedures adopted can cause some sort of damage to one's health.…”
Section: Marta Deborah and Lúciamentioning
confidence: 99%